Augmentation of labor with oxytocin and its association with delivery outcomes: A large‐scale cohort study in 12 public hospitals in Nepal. (2nd June 2020) - Litorp, Helena; Sunny, Avinash K.; Kc, Ashish
Abstract: Introduction: The use of oxytocin to augment labor is increasing in many low‐resource settings; however, little is known about the effects of such use in contexts where resources for intrapartum monitoring are scarce. In this study, we sought to assess the association between augmentation of labor with oxytocin and delivery outcomes. Material and methods: We conducted a cohort study in 12 public hospitals in Nepal, including all deliveries with and without augmentation of labor with oxytocin, but excluding elective cesarean sections, women with missing information on augmentation of labor, and women without fetal heart rate on admission. Bivariate and multivariate logistic regression calculating the crude and adjusted risk ratio (aRR) with corresponding 95% CI were performed, comparing (a) intrapartum stillbirth and first‐day mortality (primary outcome); and (b) intrapartum monitoring, mode of delivery, postpartum hemorrhage, bag‐and‐mask ventilation of the newborn, Apgar score, and neonatal death before discharge (secondary outcomes) among women with and without oxytocin‐augmented labor. Results: The total cohort consisted of 78 931 women, of whom 28 915 (37%) had labor augmented with oxytocin and 50 016 (63%) did not have labor augmented with oxytocin. Women with augmentation of labor had no increased risk of intrapartum stillbirth and first‐day mortality (aRR 1.24, 95% CI 0.65‐2.4), but decreased risks of suboptimal partograph use (aRR 0.71, 95% CI 0.68‐0.74), suboptimal fetal heart rate monitoring (aRR 0.50, 95% CI 0.48‐0.53), and emergency cesarean section (aRR 0.62, 95% CI 0.59‐0.66), and increased risks of bag‐and‐mask ventilation (aRR 2.1, 95% CI 1.8‐2.5), Apgar score <7 at 5 minutes (aRR 1.65, 95% CI 1.49‐1.86), and neonatal death (aRR 1.93, 95% CI 1.46‐2.56). Conclusions: Although augmentation of labor with oxytocin might be associated with beneficial effects, such as improved monitoring and a decreased risk of cesarean section, its use may lead to an increased risk of adverse perinatal outcomes. We urge for a cautious use of oxytocin to augment labor in low‐resource contexts, and call for evidence‐based guidelines on augmentation of labor in low‐resource settings.